Economic competence in early secondary school: Evidence from a large-scale assessment in Germany. (November 2020) - Oberrauch, Luis; Kaiser, Tim
Abstract: We employ a psychometrically validated performance test to study economic competence among representative sample of 1, 687 early secondary school students in Southwest Germany. The rich dataset allows us to study variation in economic competence across school types and observable student characteristics. Our results show that economic competence is significantly lower among female students, migrants, students with parents of low socio-economic status and those who do not attend the highest track school type. Additionally, quantile regression analyses suggest that the gender gap increases along the distribution of economic competence and that effects of parents with high socio-economic status are more pronounced above the median of the competence distribution.